A multifunctional resealable perfusion chip for cell culture and tissue engineering. Issue 32 (15th March 2016) - Lang, Qi; Ren, Yukun; Wu, Yanshuang; Guo, Yongbo; Zhao, Xin; Tao, Ye; Liu, Jiangwei; Zhao, Hong; Lei, Lei; Jiang, Hongyuan
Abstract : A multifunctional resealable perfusion chip is designed and fabricated to supply a dynamic in vitro environment to cells and tissues. Abstract : We describe a multifunctional resealable perfusion chip to mimic the human environment for cell or tissue culture in vitro and to increase the efficiency of culture in this study. To meet the culture requirement of a two-dimensional (2D) submerged cultures and an air–liquid interface perfusion cultures, a multifunctional resealable perfusion chip was designed and fabricated. Human embryonic kidney cells (HEK293T) and human colon carcinoma cells (SW620) were submerged cultured in the chip for 72 h. Cell viability and cell proliferation tests were used to evaluate the performance of the chip. Moreover, an artificial epidermis was developed, and it lasted for 7 days for the submerged culture immortal human keratinocyte (HaCaT) monolayer and 35 days for the air–liquid interface differentiated culture. The artificial epidermis cultured in the chip and in a conventional transwell were evaluated by the Live/Dead Viability/Cytotoxicity kit, histology, and hematoxylin and eosin staining. The stability and the benefits of our resealable chip were demonstrated by culture cells and epidermis tissue. Unlike a conventional static culture, no obvious advantage was observed in the 2D submerged culture of HEK293T and SW620 cells in the chip, but an outstanding advantage was observed in the 2D HaCaT cell culture with high density and a reconstructed epidermis. The cells grew well, and the epidermis was successfully reconstructed. This result implies that our multifunctional chip has great potential in cell culture and tissue engineering applications.